The effect of aloe vera plant (ALOE BARBADENSIS) extracts on sickle cell blood (hbss) - R. N1, ̊Nwaoguikpe; W2 a, Braide; T.I.N, Ezejiofor3 (Global Journal of Food and Agribusiness Management, 2011)
The phytochemical and antisickling properties of the leaf and gel extracts of the Aloe vera plant were studied. A large quantity of the plant was collected from the Herbarium of the Department of Pharmacognosy, Faculty of Pharmacy,University of Nigeria, Nsukka and authenticated by a taxonomist at the Department of Crop Science and Technology of the Federal University of Technology, Owerri as being of good quality. The phytochemical composition of the gel and leaf extracts revealed the presence of alkaloids, flavonoids, saponins, tannins and phenols at different concentrations . The determination of the antisickling effects of these extracts was directed towards the inhibition of sickle cell polymerization and the improvement of the Fe2+/Fe3+ ratio of HbSS in the presence of the extracts. Most of the antisickling amino acids identified in the extracts included: phenylalanine, arginine , tyrosine, aspartic acid , histidine and others, all at high concentrations. The relative percent inhibition of sickle hemoglobin polymerization by the extracts ranged from 77.93% for the CAE of the gel to 80.86% for that of the leaf . The Ascorbic acid concentrations of the extracts were remarkable ranging from 2.028±0.1 mg/ml for the gel to 3.631±0.1 mg/ml for the leaf. The CAE fraction of both gel and leaf improved the Fe2+/Fe3+ ratio from 46.98% for the gel to 78.0% for the leaf extracts respectively .The total vitamin C concentration of the samples expressed in mg/100g sample are : 202.8±0.1 for the gel and 199.7±0.1 for the leaf. There is no significant difference in the concentrations of the CAE fractions of the leaf and gel. Aloe vera plant extracts with the preponderance of nutrients, phytochemicals, amino acids and other compounds can be very beneficial in the management of sickle cell disease.